Decoding carbon allocation in boreal forests: Integrating multi-proxy observations and process-based modelling - Paulina F. Puchi; Daniela Dalmonech; Daniele Castagneri; Giancarlo Genovese; Warren Helgason; Myroslava Khomik; Lorenzo Brilli; Alessio Collalti (Agricultural and Forest Meteorology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Sedimentary facies and invertebrate faunal exchange confirm humid conditions in the tropical eastern Atlantic during interglacial Marine Isotopic Stage (MIS) 11c - Carlos S. Melo; José Madeira; Ricardo S. Ramalho; Ana C. Rebelo; Michael W. Rasser; Esther Martín-González; Alfred Uchman; Carlos Marques da Silva; Emílio Rolán; Luís Silva; Joseph A. Stewart; Laura F. Robinson; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Data-driven modeling of the flame composition space of an intrinsically unstable lean premixed ammonia/hydrogen/air flame - S. Bottari; F. D’Alessio; C. Matteucci; P.E. Lapenna; F. Creta (Fuel, 2026)

LP-48 Drug efficacy using high-throughput production of clonal pancreatic ductal adenocarcinoma tumoroids derived from patient and cell line within extracellular matrix microbeads - M. Frèrejacques; S. Porte; F. Bottausci; A. Pitaval; N. Dusseti; M. Alessio; M. Benessalah; F. Navarro; V. Haguet; X. Gidrol (Toxicology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Boar semen cryopreservation: State of the art, and international trade vision - A. Bolarin; J. Berndtson; F. Tejerina; S. Cobos; C. Pomarino; F. D’Alessio; H. Blackburn; K. Kaeoket (Animal Reproduction Science, 2024)

Stand age diversity (and more than climate change) affects forests’ resilience and stability, although unevenly - Elia Vangi; Daniela Dalmonech; Elisa Cioccolo; Gina Marano; Leonardo Bianchini; Paulina F. Puchi; Elisa Grieco; Alessandro Cescatti; Andrea Colantoni; Gherardo Chirici; Alessio Collalti (Journal of Environmental Management, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Crop rotational diversity can mitigate climate‐induced grain yield losses - Alessio Costa; Riccardo Bommarco; Monique E. Smith; Timothy Bowles; Amélie C. M. Gaudin; Christine A. Watson; Remedios Alarcón; Antonio Berti; Andrzej Blecharczyk; Francisco J. Calderon; Steve Culman; William Deen; et al. (Global Change Biology, 2024)
Diversified crop rotations have been suggested to reduce grain yield losses from the adverse climatic conditions increasingly common under climate change. Nevertheless, the potential for climate change adaptation of different crop rotational diversity (CRD) remains undetermined. We quantified how climatic conditions affect small grain and maize yields under different CRDs in 32 long‐term (10–63 years) field experiments across Europe and North America. Species‐diverse and functionally rich rotations more than compensated yield losses from anomalous warm conditions, long and warm dry spells, as well as from anomalous wet (for small grains) or dry (for maize) conditions. Adding a single functional group or crop species to monocultures counteracted yield losses from substantial changes in climatic conditions. The benefits of a further increase in CRD are comparable with those of improved climatic conditions. For instance, the maize yield benefits of adding three crop species to monocultures under detrimental climatic conditions exceeded the average yield of monocultures by up to 553 kg/ha under non‐detrimental climatic conditions. Increased crop functional richness improved yields under high temperature, irrespective of precipitation. Conversely, yield benefits peaked at between two and four crop species in the rotation, depending on climatic conditions and crop, and declined at higher species diversity. Thus, crop species diversity could be adjusted to maximize yield benefits. Diversifying rotations with functionally distinct crops is an adaptation of cropping systems to global warming and changes in precipitation.

Degradation of biodegradable plastics in waste management systems and the open environment: A critical review - Sevil V. Afshar; Alessio Boldrin; Thomas F. Astrup; Anders E. Daugaard; Nanna B. Hartmann (Journal of Cleaner Production, 2024)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Lessons, narratives, and research directions for a sustainable circular economy - Sina Leipold; Anna Petit‐Boix; Anran Luo; Hanna Helander; Machteld Simoens; Weslynne S. Ashton; Callie W. Babbitt; Alba Bala; Catharina R. Bening; Morten Birkved; Fenna Blomsma; Casper Boks; et al. (Journal of Industrial Ecology, 2023)
The current enthusiasm for the circular economy (CE) offers a unique opportunity to advance the impact of research on sustainability transitions. Diverse interpretations of CE by scholars, however, produce partly opposing assessments of its potential benefits, which can hinder progress. Here, we synthesize policy‐relevant lessons and research directions for a sustainable CE and identify three narratives—optimist, reformist, and skeptical—that underpin the ambiguity in CE assessments. Based on 54 key CE scholars’ insights, we identify three research needs: the articulation and discussion of ontologically distinct CE narratives; bridging of technical, managerial, socio‐economic, environmental, and political CE perspectives; and critical assessment of opportunities and limits of CE science–policy interactions. Our findings offer practical guidance for scholars to engage reflexively with the rapid expansion of CE knowledge, identify and pursue high‐impact research directions, and communicate more effectively with practitioners and policymakers.

FMRI and intra-cranial electrocorticography recordings in the same human subjects reveals negative BOLD signal coupled with silenced neuronal activity - Alessio Fracasso; Anna Gaglianese; Mariska J. Vansteensel; Erik J. Aarnoutse; Nick F. Ramsey; Serge O. Dumoulin; Natalia Petridou (Brain Structure and Function, 2022)
Positive blood oxygenation level-dependent (BOLD) responses (PBR), as measured by functional Magnetic Resonance Imaging (fMRI), are the most utilized measurements to non-invasively map activity in the brain. Recent studies have consistently shown that BOLD responses are not exclusively positive. Negative BOLD responses (NBR) have been reported in response to specific sensory stimulations and tasks. However, the exact relationship between NBR and the underlying metabolic and neuronal demand is still under debate. In this study, we investigated the neurophysiological basis of negative BOLD using fMRI and intra-cranial electrophysiology (electrocorticography, ECoG) measurements from the same human participants. We show that, for those electrodes that responded to visual stimulation, PBR are correlated with high-frequency band (HFB) responses. Crucially, NBR were associated with an absence of HFB power responses and an unpredicted decrease in the alpha power responses.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Tick species from Africa by migratory birds: a 3-year study in Italy - L. Toma; E. Mancuso; S. G. d’Alessio; M. Menegon; F. Spina; I. Pascucci; F. Monaco; M. Goffredo; M. Di Luca (Experimental and Applied Acarology, 2021)

Consequences of oxidative damage on the fatty acid profile in muscle of Cichlasoma amazonarum acutely exposed to copper - Matheus D. Baldissera; Carine F. Souza; Danilo C. Barroso; Rogério S. Pereira; Fernanda C. de Oliveira; Keiti O. Alessio; Roger Wagner; Cezar A. Bizzi; Bernardo Baldisserotto; Adalberto L. Val (Fish Physiology and Biochemistry, 2020)

Assessing the efficacy of nourishment of a Mediterranean beach using bimodal fluvial sediments and a specific placement design - Matteo Vacchi; Giorgio Berriolo; Chiara F. Schiaffino; Alessio Rovere; Edward A. Anthony; Nicola Corradi; Marco Firpo; Marco Ferrari (Geo-Marine Letters, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Solution structure and biochemical characterization of a spare part protein that restores activity to an oxygen-damaged glycyl radical enzyme - Sarah E. J. Bowman; Lindsey R. F. Backman; Rebekah E. Bjork; Mary C. Andorfer; Santiago Yori; Alessio Caruso; Collin M. Stultz; Catherine L. Drennan (JBIC Journal of Biological Inorganic Chemistry, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Radiotherapy in palliation of thoracic tumors: a phase I–II study (SHARON project) - Eleonora Farina; Gabriella Macchia; Milly Buwenge; Giambattista Siepe; Alice Zamagni; Silvia Cammelli; Savino Cilla; Tigeneh Wondemagegnhu; Aynalem A. Woldemariam; A. F. M. Kamal Uddin; Mostafà Aziz Sumon; Francesco Cellini; et al. (Clinical & Experimental Metastasis, 2018)

Short-course regimen of palliative radiotherapy in complicated bone metastases: a phase i–ii study (SHARON Project) - Jenny Capuccini; Gabriella Macchia; Eleonora Farina; Milly Buwenge; Domenico Genovesi; Luciana Caravatta; Nam P. Nguyen; Silvia Cammelli; Savino Cilla; Tigeneh Wondemagegnhu; A. F. M. Kamal Uddin; Mostafà Aziz Sumon; et al. (Clinical & Experimental Metastasis, 2018)

Multispectral analysis of Northern Hemisphere temperature records over the last five millennia - C. Taricco; S. Mancuso; F. C. Ljungqvist; S. Alessio; M. Ghil (Climate Dynamics, 2015)

Analysing chemical-induced changes in macroinvertebrate communities in aquatic mesocosm experiments: a comparison of methods - Eduard Szöcs; Paul J. Van den Brink; Laurent Lagadic; Thierry Caquet; Marc Roucaute; Arnaud Auber; Yannick Bayona; Matthias Liess; Peter Ebke; Alessio Ippolito; Cajo J. F. ter Braak; Theo C. M. Brock; et al. (Ecotoxicology, 2015)

Low-level caloric restriction rescues proteasome activity and Hsc70 level in liver of aged rats - Mara A. Bonelli; Silvia Desenzani; Gabriella Cavallini; Alessio Donati; Antonello A. Romani; Ettore Bergamini; Angelo F. Borghetti (Biogerontology, 2008)

Methionine 156 in the immunodominant domain of CD36 contributes to define the epitope recognized by the NL07 MoAb - Paola Gruarin; Daniela Ulliers; Rick F. Thorne; Massimo Alessio (Molecular and Cellular Biochemistry, 2000)